Wanita Pekerja dalam Pandangan Islam - Wati, Henny Rahma; Angraini, Refika (Masterpiece: Journal of Islamic Studies and Social Sciences, 2025)
This article examines the role and position of working women from an Islamic perspective, and provides an understanding of how religion views women's involvement in the world of work. This study aims to examine various Islamic teachings that are relevant to the issue of working women outside the home, by considering the rights, obligations, and ethics that women need to adhere to in their professional activities. The results of the study show that Islam gives women the freedom to work, as long as the work does not conflict with sharia principles, such as maintaining honor, not violating religious norms, and prioritizing family responsibilities. Therefore, the role of working women in Islamic society is acceptable, as long as it is in accordance with the limitations taught in Islam and does not harm the welfare of themselves or their families. This article is expected to contribute to enriching insight into women's involvement in the world of work from an Islamic perspective.   Abstrak Artikel ini mengkaji peran dan kedudukan perempuan pekerja dari perspektif Islam, serta memberikan pemahaman tentang bagaimana agama memandang keterlibatan perempuan dalam dunia kerja. Kajian ini bertujuan untuk mengkaji berbagai ajaran Islam yang relevan dengan persoalan perempuan pekerja di luar rumah, dengan mempertimbangkan hak, kewajiban, dan etika yang perlu dipatuhi perempuan dalam aktivitas profesionalnya. Hasil kajian menunjukkan bahwa Islam memberikan kebebasan kepada perempuan untuk bekerja, sepanjang pekerjaan tersebut tidak bertentangan dengan prinsip-prinsip syariah, seperti menjaga kehormatan, tidak melanggar norma agama, dan mengutamakan tanggung jawab keluarga. Oleh karena itu, peran perempuan pekerja dalam masyarakat Islam dapat diterima, sepanjang sesuai dengan batasan-batasan yang diajarkan dalam Islam dan tidak merugikan kesejahteraan dirinya maupun keluarganya. Tulisan ini diharapkan dapat memberikan kontribusi untuk memperkaya wawasan tentang keterlibatan perempuan dalam dunia kerja dari perspektif Islam.